Ultra-High Field MRI Technologies: Physics-Based Innovations for Early Disease Detection - Gatea, Zahraa Mohanad; Mardi, Kawthar Mohammed; Jawad, Hawraa Riyad; Lateef, Rusul Nazar; Majeed, Sajjad Khalid (American Journal of Botany and Bioengineering, 2025)
Ultra-high field (UHF) imaging systems with magnetic field strength ranging from 7-10.5 tesla (T) are now commercially available for preclinical and clinical applications. UHF magnetic resonance (MR) imaging is an emerging technology, especially of certain pathologies routinely overlooked by lower-field strength magnetic resonance systems, which would benefit from high SNR. However, the UHF transmission field in the region of the imaged anatomy is an important challenge to be addressed as increasing B0 intensities increase B1+ inhomogeneities affecting the accuracy of spin-state excitation and nullling, as well as generating local overheating. On the other hand, acquisition of the same anatomical region with UHF imagers is a challenging task since high field systems shorten T1 and T2 relaxation times. Thus, absolute quantitative measurements with UHF systems would require the implementation of correction techniques or special sequences possibly available in the proprietary sequence library, but not readily available in clinical settings. Signal-to-noise ratio increases with 7T scanners, and further, hitherto unavailable or too costly spatial resolution is attainable in conjunction with ultrafast acquisition techniques (UFT) at a motion-sensitivity similar to that of lower field strength systems. However, patient outcome will depend on a new evaluation process currently not available on the market. Highly negative non-chemically shift referenced water-only fat suppression techniques in combination with special B1 shimming methods, either via dedicated phantom or a combination of B0 and B1 field maps are urgently needed. Development of fast radiofrequency (RF) spoiling techniques on higher field platforms similar to those regularly used at lower field strength, RF coil alternatives, and parallel transmit support will be also required. Implementing water relocatable sequences and compatibility solutions with current clinical settings promises yet unqualified but predictable outcomes.